Evaluation study of mobility management protocol in NEMO - Geaiger, Mohamed; Hassan Abdalla Hashim, Aisha; Khalifa, Othman Omran; Elsheikh, Elsheikh Mohamed Ahmed (2014)
The Internet Engineering Task Force has developed Network Mobility Basic Support Protocol. One of the important issues of network mobility management schemes is the hands-off management. This paper presents the network mobility management schemes into two classifications in order to highlight the limitation and improvement of such schema and comparing different handover techniques that have been proposed to enhance the performance during handover. Finally, some common solutions have been used to solve seamless mobility related problems were briefly investigated and evaluated. However, the researchers challenge sit side of integration of these schemes. The current trend of network mobility at IP level at a huge scale relies on the ability to offer advanced mobility management that can coexist with the presently deployed protocols.